Plant metabolites and regulation under environmental stress - Ahmad, Parvaiz; Ahanger, Mohammad Abass; Singh, Vijay Pratap, 1982-; Tripathi, Durgesh Kumar; Alam, Pravej; Alyemeni, Mohammed Nasser (Elsevier Ltd. : Academic Press, 2018)
Plant Metabolites and Regulation Under Environmental Stress presents the latest research on both primary and secondary metabolites. The book sheds light on the metabolic pathways of primary and secondary metabolites, the role of these metabolites in plants, and the environmental impact on the regulation of these metabolites. Users will find a comprehensive, practical reference that aids researchers in their understanding of the role of plant metabolites in stress tolerance.